Catalytic CO2 absorption in an amine solvent using nickel nanoparticles for post-combustion carbon capture. Issue 36 (February 2020) - Seo, Seokju; Lages, Brian; Kim, Myeongsub
Highlights: Nickel nanoparticles (NiNPs) accelerates the rate of CO2 absorption into amine solvent. The experimental modeling in both limited and high mixing conditions was successfully demonstrated using microfluidics. The NiNPs' catalytic performance accelerates the average CO2 absorption rate by 34% and 54% in the limited mixing and the high mixing conditions, respectively. Abstract: In industrial post-carbon capture processes, monoethanolamine (MEA) has been mainly used as an absorption solvent. However, this approach generates significant amounts of toxic wastewater containing a heavy chemical difficult to treat and also raises concerns about acute corrosion of metal structures in the facility. To reduce the use of MEA in carbon capture, this work evaluates the catalytic performance of nickel nanoparticles (NiNPs) for CO2 capture as a possible additive in an MEA solvent. We test the CO2 absorption rate in MEA catalyzed by NiNPs in both limited and high mixing conditions to model real capturing processes in the packed column of industrial absorption reactors. For this purpose, a microreactor and a long serpentine microchannel are employed. The catalytic absorption performance of NiNPs for CO2 in aqueous MEA is evaluated using CO2 microbubbles by monitoring changes in size upon their time-dependent absorption. We find that the average CO2 absorption rate with NiNPs is accelerated by 34% in the limited mixing condition in the microreactor. This increase is mainly due to NPs' catalytic CO2 absorption driven by a Brownian motion. On the other hand, in the high mixing condition in the long serpentine microchannel, the catalytic activity of NiNPs improves the average CO2 absorption rate further to 54%. This improvement makes it possible to shorten the timescale for reaching CO2 absorption equilibrium and therefore to reduce the size of the reactors significantly. The test results demonstrate that NiNPs serve as suitable additives in the MEA-based CO2 absorption system.